Our corn heritage: a vision from cultural identity and human rights (2020)
The purpose of this reflection article is to highlight the importance of the use of native corn seeds compared to transgenic seeds in the framework of the human right to take part in the cultural life of the community, both for some populations as well as for some artists. A critical analysis is made regarding how the use of native corn seeds are an important part of social and material relations within the framework of the cultural rights of indigenous, peasant, afro communities, etc., as well as for some contemporary artists. Some contributions that stand out from art and culture, allow generating spaces to keep alive traditions, values and practices, which haunt the ancestral cultivation of corn and its multiple uses. It is concluded that the disappearance of native seeds can represent an irreparable loss of the material and immaterial wealth of these communities, so that art and culture can become a tool of resistance against the legal restrictions that some governments promote, by establish misguided trade policies for the exclusive use of transgenic seeds and that lead to the disappearance of native ones.